Technologie nostalgii. Analiza retrotopii w grze World of Warships - Kłosiński, Michał (Postscriptum Polonistyczne, 2020)
The paper presents an analysis of the ORP Błyskawica ship in World of Warships. The study concerns the retrotopian and mythological image of the replica of a real warship created in the game. The analysis and interpretation touch upon both the model of acquiring ships within the framework of playbour and the very idea of faithfully reproducing a historical artefact. The reflection concerns, therefore, virtual technology employed in the service of nostalgia and of dreams, and as a tool for constructing myths about the glorious past in which military technologies developed. For this purpose, the text introduces a new research category, namely a quasi-historical item.